Letter Norfolk Island, to Mr Sykes - Hibbins, Thomas; Sykes, James (1798)
Letter, Norfolk Island, 18th June 1798 to Mr Sykes requesting a loan and requiring him to send out specified supplies.
Manuscript reference no. : NLA MS 4179.
Copy of original.
Location of original unknown.
Nan Kivell Collection.
Keywords: Hibbins, Thomas -- Correspondence; Sykes, James -- Correspondence